The Effect of Flowrate on Dye Removal of Jumputan Wastewater in a Fixed-Bed Column by Using Adsorption Model: Experimental and Breakthrough Curves Analysis - Lia Cundari; Bazlina Dawami Afrah; Asyeni Miftahul Jannah; Patrick Rudy Meizakh; Muhammad Alik Aziz; Wulan Ayum Larasati (Reaktor, 2022)
One of the traditional arts in Indonesia is Jumputan fabric which produced by using tie and dye technic. The Jumputan wastewater contains organic compounds which can decrease the oxygen content in water. An economic and applicable process to handle the Jumputan wastewater is adsorption. The research was conducted to find out the effect of flowrate to the adsorption performance of the dye onto activated carbon in a continuous fixed-bed column based on the breakthrough curve parameter. The activated carbon made from betel nuts (Cyrtostachys lakka) with size particle of 60 mesh. The column dimension was 2 inches of inside diameter and 60 cm of height column. The bed height was 10 cm. The feed pumped from the top of column with variation of flowrate of 10, 20 and 30 ml/min. The absorbance of the dye was analyzed by using UV-Vis spectrophotometer. The adsorption column models were analyzed using Thomas, Yoon-Nelson, and Adam-Bohart. The result of this research was the dye removal efficiency decreased with the increase in flowrate, which was 61.4%; 56.9%; and 47.6% for 10, 20, and 30 ml/min respectively. Feed flowrate showed a negative effect on the saturation time, the higher the flowrate, the faster it reaches the saturation point of the adsorbent. The breakpoints were 180, 260, and 420 minutes at 30, 20, 10 ml/min flowrate. The model data indicated that Thomas and Yoon-Nelson are fitted well with the experimental results. The models show the largest regression and the smallest error with the value of each 0.99 and 0.0035 at flowrate of 10 ml/min.